Sports Tourism In Post Conflict Peace Building: Evidence From Swat, Pakistan - DOGAR, Adnan Ahmad; Noreen,; SHAH, Ikram; ELAHI, Noor (The journal of contemporary issues in business and government, 2021)
Taliban uprising in Swat followed by military operations and floods severely damaged the tourism industry of Swat. Skiing festival in Malamjabba and Aman Festival in Kalam were instrumental in bringing tourists back to Swat in post conflict scenario. The study focused on the contribution of Skiing at MalamJabba in revival of tourism and post conflict peace building. Mixed method approach was used to collect data from fifty respondents that included tourists, tourism service providers and representatives of relevant stake holders from government and private organizations. Questionnairs followed by in depth interviews were used to collect the data. Findings of the study indicated that skiing played a very important role in the revival of tourism. Most of the tourist whose primary motivation was skiing at Malamjabbaalso visited or had intentions to visit other areas of Swat. Local communities are engaged in the industry at different levels constituting about 91 percent of the total labor force. Winter sports and increasing range of tourism products means increasing tourist season in the area that provides sustainable source of livelihoods for local community. Engagement of youth in sports and income generating activities provides an important tool for the peace building in the area.